Algebra Associated with the Hasse Graph of the Hypercube - Schneider, Cary; Franko, Kelsey M.; Chan, Wai Shan (My University, 2012)
With every n-dimensional cube, there is a graph that is associated with it, a Hasse Diagram. Different levels of the Hasse graph represent how many vertices there are in the cube, how many edges, how many faces, and so on. This study sought to find the Hasse graphs of different symmetries of the cube and find the relation between them.
Color poster with text, diagrams, and formulas.
Keywords: Posters; Algebra--Graphic methods; Hypercube; Hasse diagrams